Perception of Illiterate Society Toward The Functional Literacy Program - Laksono, Bayu Adi; Supriyono, Supriyono; Wahyuni, Sri (Journal of Nonformal Education, 2018)
Perception has the important role in determining the worldview and impacts significantly, including on the functional literacy programs. The aim of this study is to reveal the perception of the illiterate in functional literacy programs. This research uses the qualitative approach with the type of phenomenology research. The research was conducted in Kadur Sub-district, Pamekasan Regency. The informants used were 6 persons who were illiterate in the functional literacy program. Data collection techniques use in-depth interviews and documentation studies. Analysis of this research data using Miles and Huberman model. The results of the study show several peceptions that formed in the functional literacy programs. Based on the research, it can be concluded that illiterate people perceive the functional literacy program as a place of fulfilment of desire, including the desire to get reward, acknowledgement, and appreciation of figure. As a place of fulfilment of needs, including the need to socialize, facing the times, empowered, and worship. The benefits of this research can be used for literacy education practitioners to improve the quality of the program by accommodating the wishes and needs of the learning community